ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DI INDONESIA (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar di BEI Tahun 2017-2019) - Clea Bunga Firstania Adiputri, - (2021)
. This research is aimed to analysed whether disclosure of corporate social responsibility is influenced by profitability, foreign ownership, managerial ownership, company size and media exposure. This research is based on the phenomenon of the extensive differences of corporate social responsibility disclosure located on the BEI company. The method use in this research are causal relationship with quantitative approach. The population in this study is manufactured company on the BEI The sampel in this research is taken by using purposive sampling method. Source data in this research obtained from the official website Bursa Efek Indonesia Stick Exchange (IDX). Data analysis in the research is done bay regression analysis. The result show that company sizee has positif effect on corporate social responsibility disclosure. Meanwhile, profitability, foreign ownership, managerial ownership and media exposure show no effect on corporate social responsibility disclosure. The result of simultan show tat profitability, foreign ownership, managerial ownership, size of the company and media exposure have an influence on corporate social responsibility disclosure.